Relationship Between Personal Hygiene During Breastfeeding And Oral Thrush In Infants 0-6 Months - Rahmadiyanti, Rahmadiyanti; Halimatussadiah, Halimatussadiah (International Journal of Health and Pharmaceutical (IJHP), 2023)
Background: Oral thrush is the infection of the mucous membranes of the baby's mouth by the Candiasis fungus which is characterized by the appearance of whitish spots and the formation of flaky plaques in the mouth so that treatment can be carried out with personal hygiene. Trush The research conducted was observational-analytic in nature. The research method used is a research method that is a type of research carried out in a case control manner, the number of samples is 60 mothers who have babies 0-6 months. In taking samples using the Lemeshow formula. Research Results: There is a relationship between education and personal hygiene with oral thrush in infants 0-6 months at the Cimarga Health Center, Lebak Regency. The OR calculation results show that mothers who have babies 0-6 months who perform personal hygiene 5.167 times do not experience oral thrush compared to experiencing oral thrush (95% CI 1.390 - 19.210) and there is no relationship between knowledge and parity with the occurrence of oral thrush. Conclusions and Suggestions: There is a relationship between personal hygiene and oral thrush, so suggestions are addressed to health workers to provide information or education about personal hygiene to nursing mothers.